Best fit membership function for designing fuzzy logic controller aided intelligent overcurrent fault protection scheme. (22nd March 2021) - Samonto, Soumyadeep; Kar, Samarjit; Pal, Sagarika; Sekh, Arif Ahmed; Castillo, Oscar; Park, Gyei‐Kark
Summary: In the present scenario, the protection system has become an important issue in the field of the power system. Intelligent protection system has been introduced in many sectors like a transmission line, distribution network, power transformer, and many more. Many researchers have published their work using low voltage DC breakers, VCB, SF6, and other areas. In the previous works, protection schemes have been developed to control the moving contacts using intelligent algorithms for tripping 100% load against phase to ground faults occurring within the system. The previous related works have introduced Trapezoidal Function and Triangular Function as inputs to the fuzzy inference system. It is also found that the Fuzzy Logic Controller has been designed by taking two inputs as current and voltage in some cases in case of overcurrent fault. The output membership function has been preferred by implementing Trapezoidal and Gaussian membership function. In this article, an overcurrent protection scheme has been discussed. The intelligent relaying technique has been introduced to trip a particular load against overcurrent fault introducing within the system. Initially, the proposed work is carried out by incorporating fuzzy logic by taking current error and current error rates as input using Gaussian membership function to the black box. Here, breaker output has been assigned using trapezoidal and triangular membership function to control the loads connected in the system. In this work, a comparative study is performed among triangular membership, trapezoidal membership, and Gaussian membership function as input function to validate the best membership function for developing any intelligent relaying algorithm against overcurrent fault. After analysis, it is considered that if a Gaussian is set to the input function and trapezoidal and triangular are set to the output function of any concerned fuzzy inference system for any overcurrent model, then the performance of tripping mechanism must show a perception level of around 99% as a quantitative measure. Experimental results validate the implementation of intelligent breaker against overcurrent faults generating within the three‐phase system. Abstract : Best Recommended Membership Function as an input to the FIS For Intelligent OC Relay.